Multifunctional Cabinet Inspired by Modern Farmhouse for Small Size Housing - Tan, Cing Qi; Selimin, Mohamad Ali; Sidek, Ahmad Anwar Safwan (Research in Management of Technology and Business, 2022)
The cost of residential property in Malaysia has continued to rise over time, resulting in more and more small apartment buildings being built to ensure that Malaysian citizens in the B40 and M40 income groups can purchase a home. Due to limited space, these are not enough to accommodate all the essential furniture and other daily necessities, especially if they have a large family, leading to the introduction of multipurpose furniture. Therefore, the objectives of this study are to identify design criteria, design and develop a prototype of a multifunctional cabinet influenced by the modern farmhouse. The study began by determining the design criteria by distributing a questionnaire to 50 people in Taiping, Perak. Then, the design and manufacturing of the prototype were carried out according to the identified design criteria. According to the survey, the majority of respondents preferred natural colors, combination of storage types and materials. The multifunctional idea includes a cabinet with storage function, a hidden dressing table and a hanging area. The new multipurpose cabinet inspired by modern farmhouse is designed to provide homeowners with a solution for small apartments without losing the utility or the desire to beautify the living space.